Insects and Human Life. - Morris, Brian (Bloomsbury Publishing, 2006)
This pioneering book looks at the importance of insects to culture. While in the developed West a good deal of time and money may be spent trying to exterminate insects, in other cultures human-insect relations can be far more subtle and multi-faceted. Like animals, insects may be revered or reviled - and in some tribal communities insects may be the only source of food available. How people respond to, make use of, and relate to insects speaks volumes about their culture. In an effort to get to the bottom of our vexed relationship with the insect world, Brian Morris spent years in Malawi, a.